Opportunities for improving the processes of preparing legal acts by public authorities based on the process mining - E. V. Vasilieva; O. I. Dolganova (Управление)
The processes of creating legal acts must meet such criteria as transparency, controllability, compliance with regulations. However, currently the procedures are extremely bureaucratic, pre-planned and go through many instances during the preparation, approval and signing. Of course, most of these processes are necessary, time-tested and legally fixed. At the same time, there are operations that require optimisation, including due to their automation or robotisation. To identify them and ensure that the procedure meet the changing needs of the state, it is important to create conditions for continuous monitoring, timely identification and operational adaptation and optimisation of the rule-making activities of the authorities. In this regard, the issue of applying contemporary technologies and approaches to analysis and the formation of recommendations for improving proactive processes seems extremely relevant. The purpose of this study is to examine the currend specifics of the preparation of the legal acts by the federal executive authorities and to identify areas for this normative documents’ improvement based on the process mining. The research methods used were a literature review and the Russian legal framework analysis, a questionnaire survey and process modelling. The authors analyse how draft legal documents (government and presidential acts, federal laws) are developed in the Russian Federation. They demonstrate the need for a transition to smart management. Its principles will ensure efficiency and flexibility in the preparation of normative legal acts. The metrics for monitoring and controlling the execution of the relevant instructions are formulated and the prospects for the development of their information support as a result of the implementation of process mining technologies are highlighted.